Circulating plasma microRNAs as a screening method for detection of colorectal adenomas. (26th February 2015) - Verma, Ajay M; Patel, Maleene; Aslam, Muhammad Imran; Jameson, John; Pringle, James Howard; Wurm, Peter; Singh, Baljit
Abstract: Background: MicroRNAs (miRNAs) are small non-coding RNA molecules. Reduced or increased levels of specific miRNAs are observed in colon and other cancers, supporting their role in carcinogenesis. Detection of colorectal polyps is the cornerstone of the Bowel Cancer Screening Programme in the UK. However, uptake of screening nationally remains under 60%. We aimed to see whether circulating plasma miRNAs can be used to screen for patients with colorectal polyps, adenomas, or both. Methods: Blood samples were taken from patients from the Bowel Cancer Screening Programme (asymptomatic but faecal occult blood testing [FOBt] positive). Plasma RNA was extracted, target miRNAs (19a, 98, 146b, 186, 191, 222*, 331-5p, 452, 625, 664, 1247) were identified on pooled case miRNA assay cards, and miRNA fraction was quantified by quantitative RT-PCR assay. Results were compared with endoscopy reports and with histology of any polyps identified and removed. Analysis was done with Excel (2011) and SPSS (version 20) software. Findings: 210 patients were included (117 with polyps, 12 with cancer, 81 healthy controls [FOBt positive]). The miRNA panel showed significant differences in expression (on t testing) for patients compared with controls for those with polyps, cancer, or both (miR-19a, p=0·0184; miR-98, p=0·0206; miR-146b, p=0·0029; miR-186, p=0·0006; miR-62, 5 p=0·0008), polyps (miR-19a, p=0·0233; miR-98, p=0·0224; miR-146b, p=0·003; miR-186, p=0·0004; miR-625, p=0·001), adenomas (miR-19a, p=0·0339; miR-98, p=0·0266; miR-146b, p=0·0045; miR-186, p=0·0008; miR-625, p=0·0049), multiple adenomas (both sides of colon; miR-146b, p=0·0194; miR-186, p=0·0226; miR-625, p=0·0013), and right-sided adenomas (miR-98, p=0·031; miR-146b, p=0·0076; miR-186, p=0·0041; miR-331-5p, p=0·0142; miR-625, p=0·0049). Receiver operating characteristic analysis showed sensitivity of 60% or more, and specificity of 86% or more for men with polyps, men with adenomas, all patients with haemorrhoids or diverticulosis and polyps, and all patients with haemorrhoids or diverticulosis and adenomas. Interpretation: The target miRNAs that we identified showed significant differences in expression levels for patients with polyps and patients with adenomas from controls. Use of this panel has potential as a screening test. Funding: Bowel Disease Research Foundation.